Association between physical activity, socioeconomic status, blood biomarkers, and diet in lebanese adults - Elie-Jacques Fares; Maria Abou Mourad; Marco Bardus; Sarah Zaki; Marie Claire Chamieh (PLoS ONE, 2025)
Background Inactivity is a significant contributor to non-communicable diseases. In Lebanon, the World Health Organization reported a rising prevalence of physical inactivity among adults. Various studies highlight the benefits of physical activity (PA) on health, influenced by sociodemographic factors, gender, age, and diet. This study aims to examine PA correlates in Lebanese adults, focusing on blood biomarkers. Methods This cross-sectional study included 296 adults aged ≥18 years. Participants completed a brief sociodemographic and food frequency questionnaire, underwent anthropometric measurements, and provided fasting blood samples. PA was measured using the International Physical Activity Questionnaire (IPAQ) short form and was divided into two categories: low PA corresponding to any walking activity, and moderate to vigorous PA for activities requiring physical effort. Descriptive statistics were computed for sociodemographic characteristics, BMI, waist circumference, energy intake, PA levels, and blood biomarkers. Logistic regressions were used to assess PA and blood biomarkers associations, adjusted for relevant covariates. Results Gender and marital status were associated with moderate to vigorous PA levels. No association was found between PA levels, BMI, waist circumference, diet, or blood biomarkers. Multivariate binary logistic regression analyses showed that females (OR=1.96, 95% CI: 1.16–3.31) and those with LDL moderate risk (OR=1.90, 95% CI: 1.02–3.66), and high risk (OR=2.44, 95% CI: 1.08–5.55), were more likely to show moderate-to-high PA levels. Conclusion PA was positively associated with gender and disease risk, particularly LDL, a biomarker known to jeopardize cardiovascular health. Disease risk appears to be a driving factor in performing physical activity among women. These results may guide early nutrition interventions endorsing physical activity as a preventive measure to decrease the prevalence of cardio metabolic disorders.